Improving silicon probe performance through layer-by-layer coating - Coelho, Nuno Miguel Teixeira (2016)
Fully comprehending brain function, as the scale of neural networks, will only be possi-ble with the development of tools by micro and nanofabrication. Regarding specifically silicon microelectrodes arrays, a significant improvement in long-term performance of these implants is essential. This project aims to create a silicon microelectrode coating that provides high-quality electrical recordings, while limiting the inflammatory response of chronic implants. To this purpose, a combined chitosan and gold nanoparticles coating was produced allied with electrodes modification by electrodeposition with PEDOT/PSS in order to reduce the im-pedance at 1kHz. Using a dip-coating mechanism, the silicon probe was coated and then charac-terized both morphologically and electrochemically, with focus on the stability of post-surgery performance in anesthetized rodents. Since not only the inflammatory response analysis is vital, the electrodes recording degradation over time was also studied. The produced film presented a thickness of approximately 50 μm that led to an increase of impedance of less than 20 kΩ in average. On a 3 week chronic implant, the impedance in-crease on the coated probe was of 641 kΩ, compared with 2.4 MΩ obtained for the uncoated probe. The inflammatory response was also significantly reduced due to the biocompatible film as proved by histological tests.